'Turning up the volume': Increasing respect for the wishes and feelings of women with intellectual impairment in decisions about their reproductive rights in England and New Zealand. (September 2021) - Manning, Joanna M
In 2004 a New Zealand Family Court Judge ordered that two extremely serious and irreversible interventions (termination of pregnancy and sterilization) be carried out on a 29-year-old woman, with mild to moderate intellectual disability, over her strenuous objection. Though her appeal was partially successful, an option which both respected her wishes and feelings and in all likelihood better promoted her best interests was not explored. A decade later, another Family Court judge held that it was in the best interests of a young woman with Down syndrome to be sterilized for contraceptive purposes, in spite of her indication that she might wish to have babies one day. The decisions were made under NZ's adult guardianship legislation, into which courts have incorporated a best interests principle, which they have interpreted broadly. But, in contrast to the Mental Capacity Act 2005 (MCA), NZ's statute lacks any requirement for decision-makers to take into account the wishes and feelings of the person with mental impairment. That requirement has been the catalyst for a more-empathetic, person-centric interpretation in English case law. Further reform to the MCA is advocated for, which would give formal primacy to P's wishes and feelings through presumptions or special phrases, as well as requiring a reasoned justification for departing from them. The Convention on the Rights of Persons with Disabilities goes even further: the article 12 right to legal capacity requires respect for the 'will and preferences' of people with mental impairments and controversially, according to the UN Committee's interpretation, requires the replacement of substitute decision-making regimes based on best interests with supported decision-making frameworks based on a person's will and preferences.